The service industries : - Channon, Derek French (Macmillan Press, 1978)
Contents: The service industries include some of Britain's most successful - retailing, construction and leisure - and some of the most controversial - insurance, transport and energy - corporations. Derek Channon's book is the first to systematically examine the strategies and structures of major firms operating in the service industries, and to identify how these factors relate to firms' actual performances. the book not only deals with the strategies and structures of individual firms, but compares and contrasts these within industry segments and in addition develops generalisations that appear to apply across industries. in particular, new correlations are established between financial performance and product and geographic diversity, formal organisation struture and leadership type.